PENGARUH TINGKAT PENDIDIKAN, PENGANGGURAN DAN UPAH MINIMUM TERHADAP TINGKAT KEMISKINAN DI PROVINSI JAWA TIMUR - Kurniawan, Septian Risky; Suparta, I Made (JEB17 : Jurnal Ekonomi dan Bisnis, 2020)
This study aims to examine Education, Unemployment, and the minimum wage on the Poverty Level in East Java Province. This study using secondary data obtained from official websites such as BPS East Java Province, and the type of data used in this study is quantitative data. The analysis technique used is multiple linear regression analysis. The results of this study indicate that: 1) Education and minimum wages partially have a positive and significant effect on the level of poverty in East Java province with a significant value of the t-test variable for the education variable obtained 0.021 (less than 0.05) and for a significant value the t-test of the minimum wage variable is sig 0.002 (less than 0.05). 2) Together (simultaneously) the effect of the application of education and the minimum wage has a positive effect while unemployment is obtained by 0.678 (greater 0.05) has an insignificant effect on the level of poverty and is significant on the level of Poverty as evidenced by the significance value of the F test of 0.001 which smaller than 0.05